Journals without Publishers: the landscape of scholar-published journals - ElSabry, ElHassan (Septentrio Conference Series, 2016)
The global move towards an “Open Access” model for journal publishing brings a new set of challenges to all those involved in scholarly communication. Of concern here is the case of journals published by one or a group of scholars, independent of any legal person (i.e. publishing house, university department, association, etc.). The question of how those journals establish and manage their venture (e.g. handling cash-flows) in absence of a legal entity is indeed an interesting one. Whether it is for ISSN registration, establishing a bank account or applying for membership to a publisher association, a legal “parent” would indeed make things easier. This project aims to explore the different strategies used by scholars to overcome this obstacle (e.g. incorporating the journal itself). It is based on a set of over 320 journals indexed by the Directory of Open Access Journals (DOAJ), where the publisher is listed as an individual person or as the journal itself. At the moment, the landscape of these journals is described, identifying their disciplines, countries, publishing platforms/software and the extent of cash flows they handle. Future steps include preparing an online survey to editors of those journals to obtain a deeper insight on their experiences as “independent” entities.